2017
DOI: 10.1111/trf.14448
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic myeloid leukemia in the setting of pregnancy: when is leukocytapheresis appropriate? A case report and review of the literature

Abstract: BACKGROUND: Chronic myeloid leukemia (CML) is a common hematologic malignancy; however, its occurrence during pregnancy is unusual due to its low prevalence in females of childbearing age. There are conflicting reports of how to best manage CML in pregnancy, particularly in the setting of leukocytosis. CASE REPORT: A 30-year-old female was diagnosed with CML at 18 weeks’ estimated gestational age. On initial presentation she reported fatigue, night sweats, and early satiety, and was found to have a white blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…253 Leukapheresis can be used for a rising white blood cell (WBC) count, although there are no data that recommend at what level of white blood cell count leukapheresis should be initiated. 249,[254][255][256] Low-dose aspirin or low-molecular-weight heparin can be considered for patients with thrombocytosis. 257,258 Monthly monitoring with qPCR and initiating treatment if the BCR-ABL1 IS increases to .1.0% is recommended.…”
Section: Treatment and Monitoring During Pregnancymentioning
confidence: 99%
“…253 Leukapheresis can be used for a rising white blood cell (WBC) count, although there are no data that recommend at what level of white blood cell count leukapheresis should be initiated. 249,[254][255][256] Low-dose aspirin or low-molecular-weight heparin can be considered for patients with thrombocytosis. 257,258 Monthly monitoring with qPCR and initiating treatment if the BCR-ABL1 IS increases to .1.0% is recommended.…”
Section: Treatment and Monitoring During Pregnancymentioning
confidence: 99%
“…Though cyclophosphamide and epirubicin are part of standard cancer treatment regimens for pregnant cancer patients[26-28], placenta toxicity following prenatal administration to these drugs is largely unexplored. The sparse studies investigating this topic showed that exposed to cyclophosphamide and epirubicine presented higher levels of apoptosis and in ammatory lesions [18,33,34]. Likewise, it is also largely unknown whether and how such placental toxicity would adversely affect the fetus.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Multiple case reports proposed leukapheresis for management of hyperleukocytosis in pregnant as leukapheresis had no adverse effect on the mother and fetus. 40 , 41 Therefore, leukapheresis was safe and also could be used for the treatment of children (excluding acute promyelocytic leukemia) and pregnant women with hyperleukocytic leukemia.…”
Section: The Application Of Leukapheresis In Hyperleukocytosismentioning
confidence: 99%